PENGARUH PENAMBAHAN SARI KURMA TERHADAP MUTU ORGANOLEPTIK DAN KANDUNGAN GIZI SUSU SARI KURMA - Christin Angelica; Junendri Ardian; Laksmi Nur Fajriani (Jurnal Pangan dan Gizi, 2025)
Anemia is still one of the main nutritional problems in Indonesia. There are innovative efforts that can be made to prevent anemia through the consumption of iron-rich foods. Sukari date juice is a form of food innovation by utilizing sukari dates which are rich in iron content (up to 6.5 mg/100 g) with low-fat milk which has the potential to prevent obesity due to excess fat which can inhibit the process of iron absorption as the main element of hemoglobin formation. This study aims to see the effect of adding sukari date juice on organoleptic and chemical quality in low-fat milk. The method used is a one-factor Complete Random Design (CRD) with 4 (four) treatments, namely the addition of 10%, 15%, 20% and 25% date juice to low-fat milk. The organoleptic test was conducted consisting of 32 semi-trained panelists. Meanwhile, the chemical quality test was carried out 2 (two) times. The results showed that the addition of date juice increased iron levels in the product, but statistically did not have a significant effect (p>0.05) which was 0.796. Proximate tests showed that the addition of date juice had a significant effect (p<0.05) on the content of water (0.004), protein (0.009), carbohydrates (0.002) and crude fiber (0.002) but no real effect (p>0.005) on ash (0.346) and fat (0.053) content.